The role of chemokines CCL3/ MIP-1 alfa and CCL4/ MIP-1 beta in pathogenesis of dry eye syndrom - Malesiński, Roman; Bakunowicz-Łazarczyk, Alina; Wysocka, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the concentration of chemokines CCL3/ MIP-1 alfa and CCL4/ MIP-1 beta in film tears in patients with dry eye syndrom. Material and methods: Tears samples were collected from 62 patients with dry eye syndrom and 18 patients from control group. The concentration of chemokines in film tears were determined by immunoenzymatic assay ELISA. Results: We found statistically increased levels of chemokines CCL3/ MIP-1 alfa and CCL4/ MIP-1 beta in film tears of patients with dry eye syndrom compared with control group. Conclusion: Inflammation may play role in pathogenesis of dry eye syndrom.